PENATALAKSANAAN APPENDICOGRAM DENGAN KLINIS APENDISITIS DI INSTALASI RADIOLOGI RSUD ARIFIN ACHMAD PROVINSI RIAU - Shelly Angella; Agus Salim; Saidatia Hawari (LPPM STIKes Awal Bros Pekanbaru, 2022)
Appendicogram is the barium appendix examination in the form of photo that can help to see blockages or dirt in the appendix. The purpose of this study was to find the Appendicogram examination management with clinical appendicitis in the Radiology Installation of Arifin Achmad Hospital, Riau Province, to find out why there were differences in appendicogram examination techniques between the theory and the Arifin Achmad Regional Hospital in Riau Province and to see the Appendicogram radiograph results with eight hours waiting time. This research is qualitative with a descriptive research design and a study case approach. The subjects used were 3 radiologists, 1 sending doctor, and 3 radiographers. The object of the study was 2 patients who had undergone an appendicogram examination with appendicitis clinical at Arifin Achmad Hospital, Riau Province. The results showed that the appendicogram examination did not need specific preparation. The patient was not subjected to plain radiographic before given contrast because plain radiographs on the appendicogram because it did not give any information. The patient was given a contrast of 50gr of barium sulfate mixed with 250ml of water. Post contrast photo 8 hours later, the reason for using 8 hours is because normal human peristalsis ranges from 6-8 hours. The results of the radiographic are visualized, namely, the contrast journey to the appendix is ​​smooth, there is no visible pressure on the cecum, the appendix is ​​not filled with contrast.